Transport mediated by electrified interfaces : studies in the linear, non-linear, and far from equilibrium regimes - Srivastava, R. C. (Studies in interface science ;, 2003)
This title provides an overview of the innovative use of electro-kinetic phenomena in experimentally exploring non-equilibrium regions of chemically non-reacting systems. Transport phenomena mediated by charged liquid-liquid interfaces and solid-liquid interfaces are also covered. Transport phenomena mediated by electrified interfaces are discussed in the context of a number of important areas, including, soil/water systems, phase transfer catalysis, animal/plant physiology and mimicking taste/smell sensing mechanisms. - Provides an overview of the innovative use of electro-kinetic phenomena - Discusses conventional electro-kinetics and other transport phenomena mediated by charged interfaces - Of special interest to those working in the area of interface science.